2019
DOI: 10.1021/acs.jafc.8b06513
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of the Neonicotinoid Insecticide Acetamiprid by Actinomycetes Streptomyces canus CGMCC 13662 and Characterization of the Novel Nitrile Hydratase Involved

Abstract: Neonicotinoid insecticide pollution in soil and water poses serious environmental risks. Microbial biodegradation is an important neonicotinoid insecticide degradation pathway in the environment. In this study, 70.0% of the acetamiprid in a 200 mg/L solution was degraded by actinomycetes Streptomyces canus CGMCC 13662 (isolated from soil) in 48 h, and the acetamiprid degradation half-life was 27.7 h. Acetamiprid was degraded to IM-1-2 ((E)-1-(1-(((6chloropyridin-3-yl)methyl)(methyl) amino)ethylidene)urea) thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 47 publications
(124 reference statements)
0
61
0
Order By: Relevance
“…The features of self-subunit swapping can be summarized as follows: (i) The metallochaperone does not deliver cobalt to the Apo-AnhA, but enables AnhA to incorporate cobalt; (ii) cobalt first inserts into the AnhAM 2 complex; (iii) the Co-bounded AnhAM 2 complex named as holoprotein (Holo)-AnhAM 2 possess cysteine-oxidized AnhA; (iv) subunit swapping occurs between an unmodified AnhA and modified AnhA; and (v) selfsubunit swapping is a subunit-specific reaction. Importantly, in contrast to all previously reported NHases, structural genes of ScNHase have the order <anhD><anhE><anhA> (Figure 1), with anhD and anhE identified as β-subunit partial peptides (Guo et al, 2019). No anhC was recognized in the ScNHase genome, and ScNHase is similar to eukaryotic NHase (Guo et al, 2019).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…The features of self-subunit swapping can be summarized as follows: (i) The metallochaperone does not deliver cobalt to the Apo-AnhA, but enables AnhA to incorporate cobalt; (ii) cobalt first inserts into the AnhAM 2 complex; (iii) the Co-bounded AnhAM 2 complex named as holoprotein (Holo)-AnhAM 2 possess cysteine-oxidized AnhA; (iv) subunit swapping occurs between an unmodified AnhA and modified AnhA; and (v) selfsubunit swapping is a subunit-specific reaction. Importantly, in contrast to all previously reported NHases, structural genes of ScNHase have the order <anhD><anhE><anhA> (Figure 1), with anhD and anhE identified as β-subunit partial peptides (Guo et al, 2019). No anhC was recognized in the ScNHase genome, and ScNHase is similar to eukaryotic NHase (Guo et al, 2019).…”
Section: Introductionmentioning
confidence: 72%
“…Importantly, in contrast to all previously reported NHases, structural genes of ScNHase have the order <anhD><anhE><anhA> (Figure 1), with anhD and anhE identified as β-subunit partial peptides (Guo et al, 2019). No anhC was recognized in the ScNHase genome, and ScNHase is similar to eukaryotic NHase (Guo et al, 2019). Therefore, investigating the post-transitional maturation of ScNHase represents a meaningful and interesting study.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Bacterial taxa that were favored by the pesticide treatment include several genera that are known to be potentially involved in neonicotinoid degradation (e.g. Hymenobacter [62], Mycobacterium [52], Pseudomonas [63], and Streptomyces [53]). In soils, there was a decline in the relative abundance of several ASVs from Proteobacteria and Gemmatimonadetes phyla and an increase in some ASVs from Chloroflexi and Actinobacteria, a result partially in accordance with a previous study that reported a decrease in the relative abundance of Gemmatimonadetes and OD1 phyla and an increase in the relative abundance of the Chloroflexi and Nitrospirae phyla in response to the neonicotinoid treatments [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the phyllosphere, 22 ASVs (mainly Bacteroidetes) were more abundant, and 12 (mainly Proteobacteria) were less abundant in response to neonicotinoid seed treatment ( Table 4) in neonicotinoid degradation (e.g. Mycobacterium [52] and Streptomyces [53]) or other pesticides degradation (e.g. Arthrobacter [54]).…”
Section: Bacterial Taxa Impacted By Neonicotinoid Seed Treatmentmentioning
confidence: 99%